Analisis Terhadap Tindak Pidana Kelalaian Oleh Anggota Militer Pada Pengadilan Militer III-16 Makassar - Pirda Tahir; Istiqamah (Alauddin Law Development Journal (ALDEV), 2022)
This study discusses Law Enforcement Against Military Members Who Commit the Crime of Negligence (Judgment Study Number: 57-K / PM.III-16 / AD / III / 2017 At Military Court III-16 Makassar) The purpose of this research is to determine and understand how the case resolution process in a military environment and the basis for judges' considerations in making decisions. This type of research is classified as qualitative or field research. The research approach used is a normative juridical approach, while the data sources of this study are primary and secondary data sources. Furthermore, the data collection methods used are interviews and documentation. This research was conducted at Military Court III-16 Makassar, by conducting direct interviews with Military Court Judges. 1) The process of settlement of criminal cases in Military III-16 Makassar is in accordance with the procedures or stages of case settlement. The case of the Crime of Negligence was investigated by POM, handed over BP to Otmil, Otmil processed the case to provide legal advice regarding the settlement of the case to PAPERA. If PAPERA agreed, Otmil submitted the case files and Skeppera to the military court. 2) The basis for the judge's consideration in making the verdict was correct because the Defendant had known and realized that he was negligent in driving which resulted in the death of another person, which he was aware of his actions and had regretted it. The implication of this research is that it can be used as a reference or input for readers and increase public confidence in the performance of military courts in handling cases, and it is hoped that it will become a lesson for military personnel to prevent similar things from happening.